ANALISIS PERTUMBUHAN EKONOMI DAN PENGEMBANGAN SEKTOR POTENSIAL DI KABUPATEN ASAHAN (PENDEKATAN MODEL BASIS EKONOMI DAN SWOT) - Taufik Zainal Abidin (Universitas Negeri Medan, 2013)
In the prespective of the otonomous region the local government has the wide authorities to arrange and manage the various government administration to the people welfare. The economic growth is one of the measuring point which is used to increase the development in a region from any kinds of the economic sector indirectly representating the economic level change in that region.The development must be appropriate with the potential condition and the developing people aspiration.When development priority is not appropriate with the each potential region then the using of resources will not be optimized. This research has a purpose to analyse how far the influence of potential sectors by using economic basis and SWOT model to the economic growth in Asahan regency.In measuring and analyzing it is used the secondary data of time series in period time of 2004-2008. The data analysis uses the Location Quotient (LQ), shift share analysis, gravitation analysis, and the SWOT analysis model. The analysis result shows that the Asahan regency has three supoerior sectors that is the agriculture, industries, electricities, gas, and water sectors where their LQ is consistenly bigger than 1 every years in the period of study. Furthermore the strategy requirement to utilize the superior sectors in Asahan Regency is the Strenghts-Opportunities (S-O) strategy.Key words: the economic growth, economic basis sector, LQ analysis, shift share analysis, gravity and SWOT analysis